Interfacial regulation and visualization of Pickering emulsion stabilized by Ca2+-triggered amphiphilic alginate-based fluorescent aggregates. (October 2021) - Lin, Feilin; Zhao, Xinyu; Yang, Shujuan; He, Furui; Qin, Wenqi; Gong, Houkui; Yu, Gaobo; Feng, Yuhong; Li, Jiacheng
Abstract: Pickering emulsions stabilized by soft particles have attracted increasing interest in research areas including food, pharmaceutics, and drug delivery. The interface-film properties have a great influence on the stability of Pickering emulsion. However, in situ studies of the stability of Pickering emulsions by direct visualization technology have not been well explored. In this work, a kind of amphiphilic alginate-based fluorescent polymer was synthesized (named Alg-TPVA) by Ugi reaction. The Alg-TPVA which can self-assemble into micellar aggregates in aqueous solution and was used to stabilize Pickering emulsion. The addition of Ca 2+ triggered the gelation of Alg-TPVA aggregates and changed the properties of the oil-water interface. The size and morphology of the Pickering emulsion were studied in detail by optical scattering and microscopy analyses. The viscoelasticity of the interface-film was characterized by rheological test. The interface-film was further characterized in situ by confocal laser scanning microscope. The spatial network structure of the interface was observed by scanning electron microscope. Results showed that the Alg-TPVA aggregates can adsorb on the oil-water interface to form an interface-film that stabilizes the emulsion. When Ca 2+ is 0.04 M, the interfacial viscoelasticity increases to the maximum, and the thickest interface-film formed rendered the best stability of Pickering emulsion. Moreover, the fluorescence-visualization technology can play a significant role in understanding emulsion stability. Graphical abstract: Image 1 Highlights: Alginate-based fluorescent polymer were synthesized via the Ugi condensation. The alginate grafted with AIE moiety showed excellent multicolor imaging properties. The synthesized polymer can stabilize the emulsion well and regulate the thickness of interface-film by calcium ions. The emulsion stability was successfully visualized using the fluorescence properties of the Alg-TPVA.